How to define the wildland-urban interface? Methods and limitations: towards a unified protocol - Gonzalez, Sofía; Ghermandi, Luciana (Frontiers in Environmental Science, 2024)
In recent decades, the risk of Wildland-Urban Interface (WUI) fires has increased due to urban growth, particularly in regions with a Mediterranean climate. The identification of the WUI is crucial for formulating fire prevention and management measures. However, there is no unified methodology for defining the WUI and it is not clear if proposals that emerge from scientific research are implemented by fire management agencies. Our objectives were to identify, describe, and compare the methods and criteria used by land and fire management agencies to define the WUI in Mediterranean-climate countries. We conducted a review of laws and fire prevention and management plans and protocols on the official websites of administrative bodies and agencies of the USA, Spain, Portugal, France, Italy, Greece, South Africa, Australia, Chile, and Argentina. Each document was read and analyzed and we conducted searches for the terminology used to name the WUI, the methodology and criteria used for defining the WUI, the fire prevention and management actions implemented in the WUI, the level of territorial organization and the responsible agencies for implementing the actions, and the presence of a methodology and a map at national scale. We found no consensus on the terminology for the WUI, the most common terms used being: wildland-urban interface, urban-rural interface, and urban-forest interface. With the exception of the USA and Portugal, there is no unified methodology at the national scale. We identified three general methods for defining the WUI: considering buffer distance for urban and vegetation areas (USA, Italy, Chile, South Africa), employing networks of strips (Spain, Portugal), and delineating risk-prone zones (Australia, France). All countries undertake fire prevention actions (e.g., fuel reduction and firebreak creation) often implemented at the municipal level. There is almost no interaction between academia and fire management agencies. Our review addresses the gap in the methods to define the WUI effectively implemented by fire management agencies. We highlight the need to implement actions aimed at enhancing the interaction between fire scientists and fire managers, which is essential for formulating and implementing effective strategies for fire prevention and optimizing resources.